First trimester serum biomarkers in pregnancies complicated with placental chronic inflammation. (October 2019) - de Moreuil, Claire; Moineau, Marie-Pierre; Padelli, Maël; Lede, Françoise; Remoue, Annabelle; Tremouilhac, Christophe; Merviel, Philippe; Pan Petesch, Brigitte; Le Moigne, Emmanuelle; Lacut, Karine; Marcorelles, Pascale
Abstract: Objective: This study aimed at determining if first trimester serum biomarkers could predict adverse pregnancy outcomes associated with villitis (VUE) and chronic intervillositis of unknown etiology (CIUE). Study design: Between January 2013 and June 2018, we selected from pathology department files placentas with VUE or CIUE associated with VUE and control placentas with available first trimester Down syndrome screening results. First trimester PAPP-A and βhCG levels were recorded. Placental growth factor (PlGF) levels were measured in patients with an available first trimester serum sample. Histological findings in placentas, course of pregnancies and newborns' characteristics were compared between cases and controls. Results: 78 cases and 75 controls were included. In cases, there were 21, 8% intrauterine growth restriction (IUGR), 30, 8% small for gestational age (SGA). Compared to controls, placentas from cases were smaller (425 g [IQR 370–480] vs 460 g [IQR 390–523], p = 0, 03), showed more maternal vascular malperfusion features (79, 5% vs 22, 7%, p < 0, 0001) and more fetal vascular malperfusion features (33, 3% vs 12%, p = 0, 002). Cases had lower PlGF (29, 74 pg/ml [IQR 19, 74–36, 17] vs 36, 37 pg/ml [IQR 27, 36–49, 13], p = 0, 007) and βhCG levels (0, 74 MoM [IQR 0, 53–1, 12] vs 1, 00 MoM [IQR 0, 72–1, 53], p = 0, 002) than controls. These differences resulted from lower PlGF levels in VUE patients compared to CIUE associated with VUE patients and controls (28, 35 vs 34, 05 and 36, 37 pg/ml, p = 0, 01) and from lower βhCG levels in CIUE associated with VUE patients compared to VUE patients and controls (0, 65 vs 0, 86 and 1, p = 0, 005). Conclusion: Low first trimester PlGF levels in cases, especially in VUE patients, suggest that reduced angiogenesis is involved in adverse pregnancy outcomes related to VUE.